Formononetin Improves the Survival of Random Skin Flaps Through PI3K/Akt-Mediated Nrf2 Antioxidant Defense System - Li, Haoliang; Jiang, Renhao; Lou, Lejing; Jia, Chao; Zou, Linfang; Chen, Mochuan (Frontiers in Pharmacology, 2022)
Random-pattern skin flap is widely used in plastic and reconstructive surgery. However, its clinical effect is limited by ischemia necrosis occurs at the distal part of flap. Previous studies have proved that the protective effect of formononetin is associated with its antioxidant, anti-inflammatory ability. However, the effect of formononetin on flap viability is unknown. Our study aimed to assess the effect of formononetin on random flap survival and the underlying mechanisms. Two doses of formononetin were administered for 7 consecutive days on flap model. Flap tissues were acquired on postoperative day 7. Our results revealed that formononetin promoted skin flap viability in a dose-dependent manner. Using immunohistochemical staining and western blot, we found that formononetin significantly reduces oxidative stress and inflammation. Hematoxylin and eosin (H&E) staining, laser Doppler images and immunofluorescence staining showed the enhancement of angiogenesis after formononetin treatment. Mechanistically, we demonstrated that formononetin’s antioxidation is mediated by activation and nuclear translocation of nuclear factor-E2-related factor 2 (Nrf2), while down-regulating cytoplasmic Kelch-like ECH-associated protein 1 (Keap1) expression. Co-treatment with formononetin and LY294002, a potent PI3K inhibitor, aborts nuclear Nrf2 expression and phosphorylated Akt, indicating that formononetin-mediated Nrf2 activation was related to PI3K/Akt pathway. Overall, our findings revealed that formononetin increases angiogenesis, reduces oxidative stress and inflammation, thus promoting flap survival. We highlighted the antioxidant effects of formononetin due to the activation of the Nrf2 system. Therefore, formononetin may be a promising candidate drug that can increase survival of random-pattern skin flaps.